Environmental social work through the African philosophy of Ubuntu: A conceptual analysis - Chigangaidze, Robert K (SAGE Publications, 2022)
Social work has been involved with the interactions between human beings and their environment since its inception. Environmental social work can expand the profession beyond its boundaries. Similarly, Ubuntu is the philosophy that has the potential to provide global messaging for the interactions between human beings and their environment. Utilizing concept analysis, this article endeavours to expand Ubuntu philosophy to the concept of Environmental Social Work. Notably, Ubuntu is relevant in the components of human relations to nature, food security, climate change, natural disasters, sustainable development and ecospiritual social work. Unequivocally, Ubuntu is a philosophy relevant to Environmental Social Work.